Inequality and Students' PISA 2018 Performance: a Cross-Country Study - Jiri Mazurek; Carlos Fernańdez Garciá; Cristina Peŕez Rico (Comparative Economic Research. Central and Eastern Europe, 2021)
The aim of this paper was to investigate the relationship between countries' PISA study results from 2018 and a set of indices related to socio-economic inequality, such as the Gini index, human development index, or gender inequality index, along with purely economic variables, such as GDP per capita and government expenditure on education. The study covered 70 countries, consisting of 37 OECD countries and 33 non-OECD countries. Research methods included multivariate linear regression models, k-means clustering, and hierarchical clustering. Our findings revealed that the Gini index was statistically insignificant, indicating income inequality had little effect on students' PISA performance. On the other hand, the gender inequality index was the single most statistically significant explanatory variable for both OECD and non-OECD countries. Therefore, our recommendation for policymakers is simple: increase students' PISA performance, thus enhancing countries' human capital and competitiveness, and focus on decreasing gender disparity and the associated loss of achievement due to gender inequality.
Keywords: I20; 330; education; gender inequality index; Gini index; inequality; PISA 2018